(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2013)
The environmentalimpact of roads (both positive and negative) include the localeffects of highways (publicroads) such as onnoise, water pollution, habitat destruction/disturbance and local air quality;and the wider effects which may include climatechange from vehicle emissions. The design, construction and managementof roads, parking andother related facilities as well as the design and regulation of vehicles canchange the impacts to varying degrees.